(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The present work intends to present some possible reflections so that we can think about terreiro clothing, mainly Umbanda, raised in the author at the beginning of her research development in the Master in Social History. For this, this research, of a bibliographical nature, assumes that reflections that transgress the coloniality of power and knowledge (QUIJANO, 2005) are necessary to think about ways of dressing of historically subaltern populations, as in the case of the communities and religiosities of African matrices, and thus relate clothing, memory, body (CALANCA, 2008; BONADIO, 2015; STALLYBRASS, 2008). Therefore, the epistemology of the macumbas thought by Simas and Rufino (2018) is used as a guide. Finally, the text presents the Nosso Sagrado Collection (Museu da República/RJ) as a possible way to think about terreiro clothing as objects of memories of Afrodiasporic experiences in Brazil.